NEW ZEALAND RABBIT’S SPERMATOZOA AFTER THE TREATMENT OF TANNIN EXTRACTION OF Pluchea indica - Eko Susetyarini; Poncojari Wahyono; Roimil Latifa; Endrik Nurrohman (BIOEDUKASI, 2020)
This current research aimed at investigating the structure and average size of New zealand rabbit’s spermatozoa. This research employed experimental design and was conducted in Chemical Engineering Laboratory of State Polytechnic of Malang and Biology Laboratory of University of Muhammadiyah Malang. This research was initiated from August to September 2019. The design of this research was specifically Completely Randomized Design, with four treatments of tannin extraction of Pluchea indica, and control with oral nasogastric with the dose of 3 ml/kgbb in four-time repetitions. A light microscope and Scanning Electron Microscope (SEM) were used for observation. One-way ANOVA was used for data analysis. As for the control group, the spermatozoa were found normal. Whilst, with reference to the three other treatments, the spermatozoa were seen to be abnormal, with apparent dilation in the neck, pseudo-droplet (bumpy neck), and dag defect (twisted tail). Based on the results, there was an influence of tannin extraction of Pluchea indica on the abnormality of New zealand rabbit’s spermatozoa (with p<0.05). Regarding the size of the spermatozoa, the average length of spermatozoa was 8.74 µm for the head, 1.86 µm for the upper neck, and 56.48 µm for the tail. With reference to HOS (Hypo-Osmotic Swelling) test, it showed that abnormal spermatozoa was in the form of severance of the head and the tail, as well as dag defect. To sum up, this research has indicated that the condensed tannin extraction contributes a similar effect to that of the pure one on the structure of spermatozoa.